Marginal bone loss around implants placed in maxillary native bone or grafted sinuses: a retrospective cohort study. Issue 3 (20th February 2013) - Galindo‐Moreno, P.; Fernández‐Jiménez, A.; Avila‐Ortiz, G.; Silvestre, F.J.; Hernández‐Cortés, P.; Wang, H.L.
Abstract: Objectives: To assess differences in marginal bone loss around implants placed in maxillary pristine bone and implants placed following maxillary sinus augmentation over a period of 3 years after functional loading. Material and methods: Two cohorts of subjects (Group 1: Subjects who received sinus augmentation with simultaneous implant placement; Group 2: Subjects who underwent conventional implant placement in posterior maxillary pristine bone) were included in this retrospective study. Radiographic marginal bone loss was measured around one implant per patient on digitized panoramic radiographs that were obtained at the time of prosthesis delivery (baseline) and 12, 24, and 36 months later. The influence of age, gender, smoking habits, history of periodontal disease, and type of prosthetic connection (internal or external) on marginal bone loss was analyzed in function of the type of osseous support (previously grafted or pristine). Results: A total of 105 subjects were included in this study. Cumulative radiographic marginal bone loss ranged from 0 mm to 3.9 mm after 36 months of functional loading. There were statistically significant differences in marginal bone loss between implants placed in grafted and pristine bone at the 12‐month assessment, but not in the subsequent progression rate. External prosthetic connection, smoking, and history of periodontitis negatively influenced peri‐implant bone maintenance, regardless of the type of osseous substrate. Conclusions: Implants placed in sites that received maxillary sinus augmentation exhibited more marginal bone loss than implants placed in pristine bone, although marginal bone loss mainly occurred during the first 12 months after functional loading. Implants with external implant connection were strongly associated with increased marginal bone loss overtime.